Pengaruh Inklusi Keuangan Terhadap Stabilitas Sistem Keuangan dan pertumbuhan Ekonomi di ASEAN - Iramayasari Iramayasari; Melti Roza Adry (Universitas Negeri Padang, 2020)
This study aims to examine the effect of financial inclusion from the amount of ATMs inclusions and the amount of bank branches inclusions on financial stability and economic growth with deposit rates in ASEAN. This study uses panel data from 2004 - 2017 consisting of 6 countries in ASEAN, that are Indonesia, Malaysia, Thailand, Singapore, Philippines and Vietnam. The data processing method uses the Simultaneous Panel. Data is obtained from World Bank publications and FRED Economic Data annually. The results of the study explained that (1) Financial inclusion has a significant influence on financial system stability in ASEAN (2) The amount of inclusion ATMs has a significant effect on financial system stability in ASEAN (3) The amount of bank branches inclusions does not have a significant effect on financial system stability in ASEAN (4) Deposit interest has a significant effect on the stability of the financial system in ASEAN (5) financial inclusion has a significant effect on economic growth in ASEAN (6) The amount of inclusion ATMs has a significant effect but has a negative relationship with economic growth in ASEAN (7) The amount of inclusion bank branches has a significant influence on economic growth in ASEAN (8) Financial system stability on economic growth has a significant positive effect simultaneously on ASEAN (9) Economic growth on financial system stability has a significant positive effect simultaneously on ASEAN.